2005
DOI: 10.1007/s11095-005-5356-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Polysorbate 80 with Erythropoietin: A Case Study in Protein–Surfactant Interactions

Abstract: Based on controlled studies, previous results suggesting that EPREX contains micelle-associated erythropoietin were incorrect. As with other surfactants and proteins, polysorbate 80 associates with erythropoietin in a defined stoichiometric ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Previous reports by other researchers on protein-surfactant interactions have suggested an estimated stoichiometry of binding. 60,62 In order to calculate stoichiometric binding of rhGH to surfactants, Bam et al made an assumption that surfactants preferentially bound to protein rather than micelles, and that surfactant binding to protein was saturable. The binding stoichiometry determination of Epoetin alfa-PS-80 by Villalobos et al implicitly suggested that similar assumptions were made.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports by other researchers on protein-surfactant interactions have suggested an estimated stoichiometry of binding. 60,62 In order to calculate stoichiometric binding of rhGH to surfactants, Bam et al made an assumption that surfactants preferentially bound to protein rather than micelles, and that surfactant binding to protein was saturable. The binding stoichiometry determination of Epoetin alfa-PS-80 by Villalobos et al implicitly suggested that similar assumptions were made.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, excipients were considered inert substances that could be used mainly in the manufacture of drug products as diluents, fillers, binders, lubricants, coatings, solvents, and dyes (7). However, with the advances in pharmaceutical science, some "active" excipients have been found to be capable of influencing drug absorption or bioavailability through a variety of mechanisms, such as modification in solubility/dissolution, change in intestinal permeability (including transporters), and modulation of gastrointestinal (GI) motility (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). To further investigate the effects of "active" excipients on the absorption of BCS class III drugs, this paper examines those that may modulate GI motility and affect the transit time of drugs in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…2 The factors that underlie immunogenicity of biomedical products can be related to the structure of protein, such as the presence of promiscuous T-cell epitopes 3 or posttranslational modifications, 4 but also to the formulation of the biomolecule. 5 Treatment-related parameters such as dosage, frequency, route of administration, and concomitant infections may also contribute to the induction of antidrug immune responses. 2 In patients with protein deficiencies administered therapeutics may be recognized by the immune system as non-self, thereby greatly increasing the risk of Ab development.…”
Section: Introductionmentioning
confidence: 99%